Distribusi Kuantitatif Logam Berat Pb dalam Air, Sedimen dan Ikan Merah (Lutjanus erythropterus) di Sekitar Perairan Pelabuhan Parepare - Surahmi Usman; Nursiah La Nafie; Musa Ramang (Marina Chimica Acta, 2013)
Research about the distribution of Pb in water, sediment and Red Snapper Fish (Lutjanus erythropterus) in the waters around the port of Parepare has been done using Atomic Absorption Spectrophotometer (AAS). Sample water, sediment and red snapper fish (Lutjanus erythropterus) was taken in three location; Ujung Lero, the residential people and traditional market.  The results showed that Pb levels in water ranged between 0.0380-0.8240 ppm, in sediments ranged between 38.9663-60.8982  mg/kg  dry  weight  while the red  snapper  fish  (Lutjanus  erythropterus)  ranged  between 4.0580-8.4590 mg/kg dry weight. Heavy metal of Pb most widely distributed in the sediment and in the water at least. The results have exceeded the threshold of water quality standards.